Establishing core data elements for colorectal cancer and mapping to FHIR resources: Towards interoperable Iranian health information systems - Raoof Nopour; Somayeh Nasiri; Maryam Ahmadi; Mohammad Shirkhoda (Journal of Education and Health Promotion)
Background: Colorectal cancer (CRC) has a high prevalence, threatening public health. Despite the high prevalence, there has not been a proper solution to standardize the data in this domain in Iran. Therefore, this study aims to provide a new approach to standardizing CRC data using Fast Healthcare Interoperability Resources (FHIR). Material and Methods: This study was conducted in five phases. First, a literature review was performed to gain the CRC core data elements based on the scientific databases and thematic websites. Second, we developed a researcher-made questionnaire with a five-choice Likert scale to gain the most important core data elements based on the opinions of specialists. Third, we leveraged the Delphi method to score these elements and develop the minimum data set (MDS) for CRC. Fourth, we used the terminologies to better perceive the concepts and thematic classification of core data elements. Fifth, we leveraged the FHIR to map the CRC core data elements to resources and standardize them. Results: Ten CRC data categories of classes were obtained from the literature review and Delphi, including administrative, diagnosis, therapeutic procedure, follow-up, patient referral, vital status, drug, clinical assessment, signs and symptoms, and history of conditions. The obtained resources were patient, care team, condition, family member history, medication request, adverse event, schedule, procedure, location, observation, diagnostic report, specimen, molecular sequence, genomic study, and service request. Conclusion: This study showed the FHIR-based standardization of the CRC data as an approach for integrating health institutions to facilitate clinical decision-making and secondary use of healthcare data.